Comparative study of self confidence and shooting efficiency of female national pistol shooters - Singh Thapa, A.; Kaur, S. (International Journal of Yogic, Human Movement and Sports Sciences, 2019)
Comparativestudy of self confidence and shooting efficiency of female national pistol shootersAnshul Singh Thapaand Sandeep KaurAbstractAim:To compare the self confidence and shooting efficiency of female pistol shooters from Delhi and Patiala. Material & Methods:The study was conducted on 100 female shooters and their age ranged 18 to 25 years. All subjects, which have been selected for sampling, participated in National or International level competitions and 50 players selected from Dashmesh Rifle club, Badal, DistrictMukatsar Sahib (Punjab) and 50 players selected from Dr. Karni Singh Shooting range, Delhi(UT). Result: It is concluded that female national pistol shooters from Punjab and female National pistol shooters from Delhihad equal level of self confidence and Shooting efficiency in match performance and shooting efficiency in single series.